Consensus on the Rational Use of Antithrombotics in Veterinary Critical Care (CURATIVE): Domain 4—Refining and monitoring antithrombotic therapies. Issue 1 (17th January 2019) - Sharp, Claire R.; deLaforcade, Armelle M.; Koenigshof, Amy M.; Lynch, Alex M.; Thomason, John M.
Abstract: Objectives: To systematically review the evidence for therapeutic monitoring of antithrombotic drugs in small animals, develop guidelines regarding antithrombotic monitoring, and identify knowledge gaps in the field. Design: First, a standardized, systematic literature review was conducted to address predefined PICO (Population/Patient, Intervention, Control, Outcome) questions, with categorization of relevant articles according to level of evidence and quality. Preliminary guidelines were developed by PICO worksheet authors and the domain chair. Thereafter, a Delphi‐style survey was used to develop consensus on guidelines regarding therapeutic monitoring of antithrombotics in dogs and cats. Setting: Academic and referral veterinary medical centers. Results: PICO questions regarding the utility of therapeutic monitoring were developed for 6 different antithrombotic drugs or drug classes, including aspirin, clopidogrel, warfarin, unfractionated heparin, the low molecular weight heparins, and rivaroxaban, The majority of the literature pertaining to therapeutic monitoring of antithrombotic drugs was either performed in experimental animal models of disease or involved studies of drug pharmacokinetics and pharmacodynamics in healthy laboratory animals. There was a paucity of high level of evidence studies directly addressing the PICO questions, which limited the strength of recommendations that could be provided. The final guidelines recommend that therapeutic monitoring should be performed when using warfarin or unfractionated heparin in dogs and cats at risk of thrombosis. There is insufficient evidence to make strong recommendations for therapeutic monitoring of aspirin or low molecular weight heparin in dogs and cats at this time. Conclusions: As in other CURATIVE domains, significant knowledge gaps were highlighted, indicating the need for substantial additional research in this field. Ongoing investigation of the role of therapeutic monitoring of antithrombotic therapies will undoubtedly facilitate improved outcomes for dogs and cats at risk of thrombosis.